The Deliberative Frugal Mindset: A model of managerial opportunity recognition for frugal innovation - Malte Krohn; Finn Petersen; Dustin Hochmuth; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2020)
The importance of growing economic powerhouses like India and China is increasing. Consequently, cost effective products and services and therefore, Frugal Innovations provide attractive business opportunities for globally operating companies. However, not all organizations seem to recognize these opportunities for what they are. The question arises if key decision makers have the right mindset to initiate and support respective innovation projects within their organizations. We take on our previous research on the Frugal Mindset and present the results of two recent studies to further develop our theory. In our first study we generate items based on the Theory of Planned Behaviour by conducting a systematic literature review of 95 publications and validate as well refine this approach in a focus group discussion with 16 experts on Frugal Innovation. Consequently, we test our research instrument for practicability, comprehensibility and further refine the items in a small scale pilot study including 8 follow-up interviews with managers from 2 multi-national companies. Based on this procedure we present a research model, a measurement instrument and first qualitative insights on the Deliberative Fugal Mindset.
Keywords: 330; Frugal Innovation; Frugal Mindset; Deliberative Frugal Mindset; Opportunity Recognition; Theory of Planned Behaviour; TPB